Gestalt therapy around the world - O'Leary, Eleanor (Chichester, West Sussex, UK ; Malden, MA : John Wiley & Sons, Inc., 2013)
The first internationally focused book on gestalt therapy to provide a comprehensive overview of current practice around the world. Features coverage of the history, training, theoretical contributions, and research initiatives relating to gestalt therapy in seventeen countriesPoints to future directions and challengesIncludes extensive information on worldwide gestalt associations, institutes, and professional societies that promote the development of the approach.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Gestalt therapy -- Cross-cultural studies; Electronic books; Cross-cultural studies